Comparison of Dydrogesterone and Medroxyprogesterone in the Progestin-Primed Ovarian Stimulation Protocol for Patients With Poor Ovarian Response - Zhang, Junwei; Du, Mingze; Li, Zhen; Liu, Wenxia; Ren, Bingnan; Zhang, Yuchao; Guan, Yichun (Frontiers in Endocrinology, 2021)
Objective: To compare the clinical outcomes of dydrogesterone (DYG) and medroxyprogesterone (MPA) in the progestin-primed ovarian stimulation (PPOS) protocol for patients with poor ovarian response (POR). Patients and methods: This was a retrospective cohort study. Women with POR who underwent IVF/ICSI at the Reproductive Center of Third Affiliated Hospital of Zhengzhou University between January 2020 and January 2021 were included. The primary outcome measure of our study was the number of oocytes retrieved. The secondary outcome measures in the present study were the number of 2PN, number of available embryos, oocyte retrieval rate, fertilization rate, viable embryo rate per oocyte retrieved, cancellation rate and pregnancy outcomes of the first embryo transfer cycle, including the biochemical pregnancy, clinical pregnancy and miscarriage rates. Results: In total, 118 women underwent hMG +DYG protocols, and 692 women who underwent hMG +MPA met the Bologna criteria for POR. After baseline characteristics were balanced using the PSM model, 118 hMG +DYG protocols were matched to 118 hMG +MPA protocols, and the baseline characteristics were comparable between the two groups. The numbers of oocytes retrieved, 2PN, and available embryos and the oocyte retrieval rate, fertilization rate, viable embryo rate per oocyte retrieved and cancellation rate of the hMG+DYG and hMG+MPA protocols were comparable. Altogether, 66 women in the hMG+DYG group and 87 women in the hMG+MPA group underwent first embryo transfers. In the hMG+DYG group, 81.8% (54/66) of the patients underwent cleavage embryo transfers; similarly, 79.3% (69/87) of patients in the hMG+MPA group had cleavage embryo transfers (P=0.70).The biochemical pregnancy rate of the hMG+DYG group was 42.4%, and this was comparable to the rate in the hMG+DYG group, at 34.5% (P=0.32). The clinical pregnancy rates were similar between the two groups (36.4% vs. 31.0%, P=0.49), and there was no significant difference in the rate of miscarriage between the two groups (12.5% vs. 29.6%, P=0.14). Conclusion: For women with POR, the clinical outcome of the hMG + DYG group was similar to that of the hMG + MPA group, indicating that both combinations can be useful options for PPOS protocols.